STAGES OF GRIEF REFLECTED THROUGH WISDOMS IN MITCH ALBOM’S TUESDAYS WITH MORRIE - Gamelia, Syifa Ravina; Istiani , Imas (Universitas PGRI Palembang, 2025)
This study explores the embodiment of Elisabeth Kübler-Ross’s five stages of grief denial, anger, bargaining, depression, and acceptance—through the philosophical insights of Morrie Schwartz as depicted in Mitch Albom’s Tuesdays with Morrie. Emphasizing the transformative power of Morrie’s reflections on mortality, the research reveals an unconventional approach to grieving that centers on acceptance, compassion, and introspection. Departing from the conventional portrayal of grief as a tumultuous emotional journey, Morrie’s perspective reframes terminal illness as an opportunity for profound emotional clarity and growth. Utilizing a qualitative literary analysis, the study investigates the extent to which Morrie’s emotional trajectory aligns with or diverges from Kübler-Ross’s framework. The analysis finds that Morrie’s experience of grief unfolds in a fluid, contemplative fashion, offering a nuanced understanding of how inner wisdom can mitigate the psychological burden of impending death.